A novel formulation of the flexural overstrength factor for steel beams - Mermerdaş, Kasım; Güneyisi, Esra Mete; D'Aniello, Mario; Landolfo, Raffaele (My University, 2013)
The ductile design of steel structures is directly influenced by the flexural behaviour of steel beams,which should be sufficient to allowplastic hinges to rotate until the collapsemechanismis completely developed. To guarantee the achievement of such a performance, the beam flexural overstrength must be quantified to appropriately apply capacity design principles. To this aim, analytical formulations to predict the flexural overstrength factor (s) of steel beams with a wide range of cross-section typologies (I and H sections, square and rectangular hollow sections) were developed based on gene expression programming (GEP). An experimental database was gathered from the available literature and processed to obtain the training and testing databases for the derivation of the closed-form solution through GEP. The independent variables used for the development of the prediction models were the geometric properties of the sections, the mechanical properties of the material, and the shear length of the steel beams. The predictions of the proposed GEP-based models were compared with the results obtained using the existing analytical equations proposed in the current literature. Comparative analysis revealed that the proposed formulation provides a more accurate prediction of beam overstrength.
Keywords: Analytical modelling; Flexural overstrength; Experimental database; Steel beams; Steel structures